Degradation of Transformer Oil (PCB Compounds) by Microwave Radiation, Ethanol Solvent, Hydrogen Peroxide and Dioxide Titanium for Reducing Environmental Hazards - Reza Tajik (Iranian Journal of Toxicology, 2013)
Background: Poly chlorinated biphenyls (PCBs) are a class of chlorinated organic chemicals that do not easily degrade in the environment. This study was conducted to determine the effect of microwave rays, hydrogen peroxide, dioxide titanium and ethanol solvent on the degradation of PCBs. Methods: A 900w domestic MW oven with a fixed frequency of 2450 MHZ was used to provide MW irradiation. Ray powers were used in 540, 720, and 900w. A hole was made on the top portion of the oven and a Pyrex vessel reactor (250ml volume) was connected to condensing system with a Pyrex tube connector. The PCBs were analyzed by GC-ECD. Results: The degradation of total PCBs was 54.62%, 79.71%, and 95.76% in terms of their ratio to solvent with transformer oil at 1:1, 2:1, and 3:1, respectively. The degradation of total PCBs was 84.27%, 89.18%, and 96.1% when using 540, 720, and 900W microwave radiation, respectively. The degradation of total PCBs was 70.72%, 93.02%, 94.16, 95.23% and 96.1% when not using H2O2/ Tio2 and using 20% H2O2 and 0.05, 0.1, 0.15, and 0.2g Tio2, respectively. Conclusion: In the present study, the optimum conditions to decompose PCBs efficiently included 50 ml volume of ratio to solvent with transformer oil (3:1), sodium hydroxide solution (0.2N) 1 cc, use of 20% hydrogen peroxide of total volume of samples, dioxide titanium (0.2g), and irradiation for 9 minutes. Under these optimum conditions, efficiency of PCBs decomposition increased.